PERBANDINGAN KUALITAS PELAYANAN INDOMARET, ALFAMART DAN SWALAYAN TERHADAP KEPUASAN KONSUMEN DI KECAMATAN TAMPAN PEKANBARU - Meldawati Meldawati; Suarman Suarman; RM Riadi RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The study aims to compare the quality of Indomaret, Alfamart and Self-service services to customer satisfaction in the Sub-distric Tampan Pekanbaru. This research was conducted on Indomaret, Alfamart and Self-service on the road Suka Karya Sub-distric Tampan with 90 research samples obtained using accidental sampling. The data used are primary data and secondary data with methods of collecting data using questionnaires and observations. The technical analysis of the data used is the analysis of the validity test, reliability test, normality test and partial difference test (independent sample t test). The results of this study indicate that from the results of different tests for level of Indomaret, Alfamart and Self-service in the Sub-distric Tampan Pekanbaru there are significant differences in the quality of service to Indomaret, Alfamart and Self-Sevice in Sub-distric Tampan Pekanbaru. From the results of the study it was found that Indomaret had better service than Alfamart and Self-service in Sub-distric Tampan Pekanbaru.Key Words : Service Quality (tangible, reliability, responsivenes, assurance, empathy),Customer Satisfactio